An Encounter with the Dead and a Fantasy of Communication: Intersubjectivity of Elegiac Poetry - Komura, Toshiaki (eTopia, 2010)
In his essay, “Autobiography as a De-facement,” Paul de Man comments on the elegiacprosopopoeia as follows: “the latent threat that inhabits prosopopoeia, namely that by making thedead speak, the symmetrical structure of the trope implies, by the same token, that the living arestruck dumb, frozen in their own death” (1979: 928). In this view, by becoming a mouthpiece forthe dead, the living elegist enters the world of death. This idea has formed the basis for ourcurrent theorization of elegy as a point of intersection between the dead and the living, a medium of communication between the two.